The Effectiveness of the Notary Code of Ethics on Administratively Just Public Services - Bianty, Thisia; Lie, Gunardi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The Notary Code of Ethics is an essential instrument for maintaining professional integrity and ensuring public services that comply with the principles of administrative justice. However, social developments, technological advancements, and the increasing complexity of legal relations necessitate an evaluation of the code’s practical effectiveness. This study aims to analyze the extent to which the Notary Code of Ethics functions as an effective guideline in delivering accountable, diligent, and non-discriminatory public services, as well as to identify the factors that influence its effectiveness. This research employs a normative juridical method using a statutory approach, a conceptual approach, and a comparative analysis of administrative justice principles. Data were obtained through a literature review of relevant legal regulations and scholarly references. The findings indicate that the effectiveness of the code of ethics is significantly influenced by the integrity and competence of notaries, the culture of the professional organization, the strength of regulations and supervisory mechanisms, and the challenges posed by the digitalization of legal services. Ethical violations such as drafting deeds without the presence of parties, document manipulation, and excessive promotion indicate a persistent gap between ethical norms and practical implementation. The study concludes that enhancing the effectiveness of the Notary Code of Ethics requires strengthening professional integrity, updating adaptive ethical norms, enforcing stricter supervision, and improving notaries’ digital capabilities to maintain the quality of public services grounded in administrative justice.